Fasilitasi Bantuan Usaha Ekonomi Kreatif Kelompok Masyarakat Binaan Balai Taman Nasional Bunaken di Pulau Nain - Ermas Isnaeni Lukman; Adi Tri Utomo; Eko Wahyu Handoyo; Yuyun Saepul Uyun; Ifan Renova Sinaga (IAI Darussalam, 2022)
Community empowerment through the development of the creative economy is an alternative for the community in developing their local potential. Economic crises have a serious impact on the future of the existence of the national park, namely the level of education of the people in and around the conservation area. Recognizing the above, Bunaken National Park Center distributes various kinds of assistance for empowering community economic enterprises through fostered groups in all areas of management at the site level (resort). Groups that have been assisted previously for a sufficient period will then be tested for feasibility and readiness in terms of receiving assistance. The implementation of facilitation activities and the provision of creative economic business assistance to the assisted village community groups on Nain Island is carried out on an ongoing basis. The method of implementing the activities is in the form of data collection and group assistance. The Sinar Bahari Nain group has indeed been facilitated in receiving assistance for capital stimulus for creative economy businesses. Assistance to community groups needs to be carried out routinely and attached after the provision of assistance and supervised in its use.